Nonlinear Dielectric Nanoresonators and Metasurfaces: Toward Efficient Generation of Entangled Photons - Sharapova, Polina R.; Kruk, Sergey S.; Solntsev, Alexander S. (Laser & Photonics Reviews)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, A. N.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Two-Colour Spectrally Multimode Integrated SU(1,1) Interferometer - Ferreri, Alessandro; Sharapova, Polina R. (Symmetry)
Multimode integrated interferometers have great potential for both spectral engineering and metrological applications. However, the material dispersion of integrated platforms constitutes an obstacle that limits the performance and precision of such interferometers. At the same time, two-colour nonlinear interferometers present an important tool for metrological applications, when measurements in a certain frequency range are difficult. In this manuscript, we theoretically developed and investigated an integrated multimode two-colour SU(1,1) interferometer operating in a supersensitive mode. By ensuring the proper design of the integrated platform, we suppressed the dispersion, thereby significantly increasing the visibility of the interference pattern. The use of a continuous wave pump laser provided the symmetry between the spectral shapes of the signal and idler photons concerning half the pump frequency, despite different photon colours. We demonstrate that such an interferometer overcomes the classical phase sensitivity limit for wide parametric gain ranges, when up to 3×104 photons are generated.
Keywords: Physics and Astronomy (miscellaneous); General Mathematics; Chemistry (miscellaneous); Computer Science (miscellaneous)

Steady states of Λ-type three-level systems excited by quantum light with various photon statistics in lossy cavities - Rose, Hendrik; Tikhonova, O V; Meier, Torsten; Sharapova, Polina (New Journal of Physics)
Abstract The interaction between quantum light and matter is being intensively studied for systems that are enclosed in high- Q cavities which strongly enhance the light–matter coupling. Cavities with low Q -factors are generally given less attention due to their high losses that quickly destroy quantum systems. However, bad cavities can be utilized for several applications, where lower Q -factors are required, e.g., to increase the spectral width of the cavity mode. In this work, we demonstrate that low- Q cavities can be beneficial for preparing specific electronic steady states when certain quantum states of light are applied. We investigate the interaction between quantum light with various statistics and matter represented by a Λ-type three-level system in lossy cavities, assuming that cavity losses are the dominant loss mechanism. We show that cavity losses lead to non-trivial electronic steady states that can be controlled by the loss rate and the initial statistics of the quantum fields. We discuss the mechanism of the formation of such steady states on the basis of the equations of motion and present both analytical expressions and numerical simulations for such steady states.
Keywords: General Physics and Astronomy

Theoretical analysis of correlations between two quantum fields exciting a three-level system using the cluster-expansion approach - Rose, Hendrik; Tikhonova, Olga V.; Meier, Torsten; Sharapova, Polina (Ultrafast Phenomena and Nanophotonics XXVI)

Two-Mode Photon-Number Correlations Created by Measurement-Induced Nonlinearity - Meier, Torsten; Hoepker, Jan Philipp; Protte, Maximilian; Eigner, Christof; Silberhorn, Christine; Sharapova, Polina R.; Sperling, Jan; Bartley, Tim (Conference on Lasers and Electro-Optics: Applications and Technology)
We demonstrate theoretically and experimentally complex correlations in the photon numbers of two-mode quantum states using measurement-induced nonlinearity. For this, we combine the interference of coherent states and single photons with photon sub-traction.

Flexible source of correlated photons based on LNOI rib waveguides - Ebers, Lena; Ferreri, Alessandro; Hammer, Manfred; Albert, Maximilian; Meier, Cedrik; Förstner, Jens; Sharapova, Polina R. (Journal of Physics: Photonics)
Lithium niobate on insulator (LNOI) has a great potential for photonic integrated circuits, providing substantial versatility in design of various integrated components. To properly use these components in the implementation of different quantum protocols, photons with different properties are required. In this paper, we theoretically demonstrate a flexible source of correlated photons built on the LNOI waveguide of a special geometry. This source is based on the parametric down-conversion (PDC) process, in which the signal and idler photons are generated at the telecom wavelength and have different spatial profiles and polarizations, but the same group velocities. Distinguishability in polarizations and spatial profiles facilitates the routing and manipulating individual photons, while the equality of their group velocities leads to the absence of temporal walk-off between photons. We show how the spectral properties of the generated photons and the number of their frequency modes can be controlled depending on the pump characteristics and the waveguide length. Finally, we discuss special regimes, in which narrowband light with strong frequency correlations and polarization-entangled Bell states are generated at the telecom wavelength.
Keywords: tet_topic_waveguide

Multimode integrated SU(1,1) interferometer - Ferreri, A.; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina (Conference on Lasers and Electro-Optics)
We present a frequency multimode integrated SU (1,1) interferometer with a polarization converter and strong signal-idler photon correlations. Phase sensitivity below the shot noise limit is demonstrated, various filtering and seeding strategies are discussed.

Spectrally multimode integrated SU(1,1) interferometer - Ferreri, Alessandro; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina R. (Quantum)
Nonlinear SU(1,1) interferometers are fruitful and promising tools for spectral engineering and precise measurements with phase sensitivity below the classical bound. Such interferometers have been successfully realized in bulk and fiber-based configurations. However, rapidly developing integrated technologies provide higher efficiencies, smaller footprints, and pave the way to quantum-enhanced on-chip interferometry. In this work, we theoretically realised an integrated architecture of the multimode SU(1,1) interferometer which can be applied to various integrated platforms. The presented interferometer includes a polarization converter between two photon sources and utilizes a continuous-wave (CW) pump. Based on the potassium titanyl phosphate (KTP) platform, we show that this configuration results in almost perfect destructive interference at the output and supersensitivity regions below the classical limit. In addition, we discuss the fundamental difference between single-mode and highly multimode SU(1,1) interferometers in the properties of phase sensitivity and its limits. Finally, we explore how to improve the phase sensitivity by filtering the output radiation and using different seeding states in different modes with various detection strategies.

Managing spectral properties and Schmidt mode content of squeezed vacuum light using sum-frequency converter - Sukharnikov, Vladislav; Sharapova, Polina; Tikhonova, Olga (Optics & Laser Technology)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Quantum optical coherence: From linear to nonlinear interferometers - Luo, Kai Hong; Santandrea, Matteo; Stefszky, Michael; Sperling, Jan; Massaro, Marcello; Ferreri, Alessandro; Sharapova, Polina; Herrmann, Harald; Silberhorn, Christine (Physical Review A)

Dark-state and loss-induced phenomena in the quantum-optical regime of Λ-type three-level systems - Rose, Hendrik; Popolitova, D. V.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Bright correlated twin-beam generation and radiation shaping in high-gain parametric down-conversion with anisotropy - Riabinin, M.; Sharapova, Polina; Meier, Torsten (Optics Express)
Uniaxial anisotropy in nonlinear birefringent crystals limits the efficiency of nonlinear optical interactions and breaks the spatial symmetry of light generated in the parametric down-conversion (PDC) process. Therefore, this effect is usually undesirable and must be compensated for. However, high gain may be used to overcome the destructive role of anisotropy in order to generate bright two-mode correlated twin-beams. In this work, we provide a rigorous theoretical description of the spatial properties of bright squeezed light in the presence of strong anisotropy. We investigate a single crystal and a system of two crystals with an air gap (corresponding to a nonlinear SU(1,1) interferometer) and demonstrate the generation of bright correlated twin-beams in such configurations at high gain due to anisotropy. We explore the mode structure of the generated light and show how anisotropy, together with crystal spacing, can be used for radiation shaping.
Keywords: Atomic and Molecular Physics; and Optics

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (Journal of Physics Communications)

Excitation of an electronic band structure by a single-photon Fock state - Rose, H.; Vasil'ev, A.N.; Tikhonova, O.V.; Meier, Torsten; Sharapova, Polina R.
In this report, we consider a semiconductor nanostructure in an optical cavity that is coupled to quantum light. We describe the semiconductor nanostructure with a parabolic band structure in a 1D k-space, while we assume a single-mode quantum field. The 1D system is chosen for simplicity in both the analytical and the numerical treatment and paves the way for the description of 2D structures in the future. Therefore, instead of using parameters which are realistic for 1D systems, we rather use parameters which qualitatively correspond to 2D GaAs structures.

Properties of bright squeezed vacuum at increasing brightness - Sharapova, Polina R.; Frascella, G.; Riabinin, M.; Pérez, A. M.; Tikhonova, O. V.; Lemieux, S.; Boyd, R. W.; Leuchs, G.; Chekhova, M. V. (Physical Review Research)
Keywords: General Engineering

Spatial entanglement and state engineering via four-photon Hong–Ou–Mandel interference - Ferreri, A; Ansari, V; Brecht, Benjamin; Silberhorn, Christine; Sharapova, Polina R. (Quantum Science and Technology)
Abstract The phenomenon of entanglement is the basis of quantum information and quantum communication processes. Entangled systems with a large number of photons are of great interest at present because they provide a platform for streaming technologies based on photonics. In this paper we present a device which operates with four-photons and based on the Hong–Ou–Mandel interference. The presented device allows to maximize the degree of spatial entanglement and generate the highly entangled four-dimensional Bell states. Furthermore, the use of the interferometer in different regimes leads to fast interference fringes in the coincidence probability with period of oscillations twice smaller than the pump wavelength. We have a good agreement between theoretical simulations and experimental results.
Keywords: Electrical and Electronic Engineering; Physics and Astronomy (miscellaneous); Materials Science (miscellaneous); Atomic and Molecular Physics; and Optics

Generating two-mode squeezing and Schrödinger cat states with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten
Keywords: pc2-ressources

Temporally multimode four-photon Hong-Ou-Mandel interference - Ferreri, Alessandro; Ansari, V.; Silberhorn, Christine; Sharapova, Polina R. (Physical Review A)

Nonlinear integrated quantum electro-optic circuits - Luo, Kai-Hong; Brauner, Sebastian; Eigner, Christof; Sharapova, Polina; Ricken, Raimund; Meier, Torsten; Herrmann, Harald; Silberhorn, Christine (Science Advances)
An integrated chip with quantum state generation, active polarization manipulation, and precise time control is demonstrated.
Keywords: Multidisciplinary

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (arXiv:1912.09097)
Measurement-induced nonclassical effects in a two-mode interferometer are investigated theoretically using numerical simulations and analytical results. We demonstrate that for certain parameters measurements within the interferometer lead to the occurrence of two-mode squeezing. The results strongly depend on the detection probability, the phase inside the interferometer, and the choice of the input states. The appropriate parameters for maximized squeezing are obtained. We analyze the influence of losses and confirm that the predicted effects are within reach of current experimental techniques.

Bright squeezed vacuum in a nonlinear interferometer: Frequency and temporal Schmidt-mode description - Sharapova, Polina R.; Tikhonova, O. V.; Lemieux, S.; Boyd, R. W.; Chekhova, M. V. (Physical Review A)

Manipulation of Two-Photon Interference by Entanglement - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Silberhorn, Christine; Meier, Torsten (Conference on Lasers and Electro-Optics)

Monolithically Integrated Hong-Ou-Mandel Experiment in LiNbO3 - Luo, Kai Hong; Brauner, Sebastian; Eigner, Christof; Sharapova, Polina; Ricken, Raimund; Meier, Torsten; Herrmann, Harald; Silberhorn, Christine (Conference on Lasers and Electro-Optics)

Orbital angular momentum modes of high-gain parametric down-conversion - Beltran, Lina; Frascella, Gaetano; Perez, Angela M; Fickler, Robert; Sharapova, Polina; Manceau, Mathieu; Tikhonova, Olga V; Boyd, Robert W; Leuchs, Gerd; Chekhova, Maria V (Journal of Optics)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Coherent control of atomic qubits by non-classical light - Balybin, Stepan N.; Sharapova, Polina; Tikhonova, Olga V. (The European Physical Journal D)
Keywords: Atomic and Molecular Physics; and Optics

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Modified two-photon interference achieved by the manipulation of entanglement - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Silberhorn, Christine; Meier, Torsten (Physical Review A)

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Engineering the Frequency Spectrum of Bright Squeezed Vacuum via Group Velocity Dispersion in an SU(1,1) Interferometer - Lemieux, Samuel; Manceau, Mathieu; Sharapova, Polina; Tikhonova, Olga V.; Boyd, Robert W.; Leuchs, Gerd; Chekhova, Maria V. (Physical Review Letters)
Keywords: General Physics and Astronomy

Tunable optical parametric generator based on the pump spatial walk-off - Cavanna, Andrea; Just, Felix; Sharapova, Polina; Taheri, Michael; Leuchs, Gerd; Chekhova, Maria V. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Giant narrowband twin-beam generation along the pump-energy propagation direction - Pérez, Angela M.; Spasibko, Kirill Yu; Sharapova, Polina; Tikhonova, Olga V.; Leuchs, Gerd; Chekhova, Maria V. (Nature Communications)
Abstract Walk-off effects, originating from the difference between the group and phase velocities, limit the efficiency of nonlinear optical interactions. While transverse walk-off can be eliminated by proper medium engineering, longitudinal walk-off is harder to avoid. In particular, ultrafast twin-beam generation via pulsed parametric down-conversion and four-wave mixing is only possible in short crystals or fibres. Here we show that in high-gain parametric down-conversion, one can overcome the destructive role of both effects and even turn them into useful tools for shaping the emission. In our experiment, one of the twin beams is emitted along the pump Poynting vector or its group velocity matches that of the pump. The result is markedly enhanced generation of both twin beams, with the simultaneous narrowing of angular and frequency spectrum. The effect will enable efficient generation of ultrafast twin photons and beams in cavities, waveguides and whispering-gallery mode resonators.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Projective filtering of the fundamental eigenmode from spatially multimode radiation - Pérez, A. M.; Sharapova, Polina; Straupe, S. S.; Miatto, F. M.; Tikhonova, O. V.; Leuchs, G.; Chekhova, M. V. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Direct Schmidt number measurement of high-gain parametric down conversion - Dyakonov, I V; Sharapova, Polina; Iskhakov, T Sh; Leuchs, G (Laser Physics Letters)
Keywords: Physics and Astronomy (miscellaneous); Instrumentation

Schmidt modes in the angular spectrum of bright squeezed vacuum - Sharapova, Polina; Pérez, A. M.; Tikhonova, O. V.; Chekhova, M. V. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Interaction of a classical laser field with a model Rydberg atom in a mixed state prepared by entanglement with few-photon quantum light - Sharapova, Polina; Tikhonova, O V (Journal of Physics: Conference Series)
Keywords: General Physics and Astronomy

Bright squeezed-vacuum source with 11 spatial mode - Pérez, A. M.; Iskhakov, T. Sh.; Sharapova, Polina; Lemieux, S.; Tikhonova, O. V.; Chekhova, M. V.; Leuchs, G. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Coherent control of interaction and entanglement of a Rydberg atom with few photons - Sharapova, Polina; Tikhonova, O V (Laser Physics Letters)
Keywords: Physics and Astronomy (miscellaneous); Instrumentation

Dynamics of ionisation and entanglement in the 'atom + quantum electromagnetic field' system - Sharapova, Polina; Tikhonova, O V (Quantum Electronics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Statistical and Nonlinear Physics; Electronic; Optical and Magnetic Materials